Simple Bone Cyst Treated with Percutaneous Steroid Injection - Fauzi Kamal, Achmad; Ajiantoro, Ajiantoro; Prabowo, Yogi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Through this study, we want to explore the effectiveness of methylprednisolone injections to treat simple bone cyst (SBC). Methods: We collected the data of all patients with SBC who were treated with percutaneous steroid injection (PSI). The study was conducted in Cipto Mangunkusumo Hospital and we used a computerized search of operative reports to identify all SBC patients who were treated by PSI 3 times between 2013 and 2016. Results: A total of 10 patients were reported in these serial cases, 8 males and 2 females. The average age of these subjects is 7.8 years old. Musculoskeletal Tumor Society functional score determine good result after 3rd injection of steroid. Bone healing evaluation using Chang Criteria showed a good healing proccess. Conclusion: Steroid injection therapy for SBC yielded a good functional result. It gets solid union relatively quickly, simple operation procedure, widely available, with less side effect. Therefore, this procedure could be a choice for treatment of SBCs patient. Further study needs to be conducted with more sample size.